Ethics in finance - Boatright, John Raymond (Blackwell Publication, 2008)
"This second edition of the ground-breaking Ethics in Finance is an up-to-date, valuable addition to the emerging field of finance ethics. Citing examples of the scandals that have shaken public confidence in Wall Street, John R. Boatright explains the importance of ethics in the operation of financial markets and institutions and in the conduct of finance professionals." "Focusing on standards of fairness in market transactions and the duties of fiduciaries and agents in financial relationships, the author introduces a broad range of practical issues related to financial markets, the financial services industry, investment decision making, and corporate financial management. In addition to the topics considered in the first edition, including unethical sales practices, insider trading, the abuse of bankruptcy, and hostile takeovers, the second edition of Ethics in Finance has a broadened scope, incorporating new discussions of issues in mutual funds, conflict of interest, and the financial theory of the firm." "This timely and comprehensive book provides an analysis of ethical issues in finance, suitable for students of finance and business ethics as well as anyone involved in financial activities."--Jacket.